2009
DOI: 10.4067/s0718-07642009000600002
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento de Catalizadores PtMo/g-Al2O3-B2O3 en Reacciones de Hidrodesaromatización de Naftaleno e Hidrodesulfuración de Dibenzotiofeno

Abstract: Resumen Con el propósito de estudiar la funcionalidades de catalizadores de hidrodesulfuración (HDS), se prepararon catalizadores PtMo/γ-Al 2 O 3-B 2 O 3 , con diferentes concentraciones de Mo y B, y se ensayaron en reacciones de hidrodesaromatización (HDA) de naftaleno en presencia de H 2 S, y HDS de dibenzotiofeno (DBT). Se observó que bajo las condiciones típicas del proceso de hidrotratamiento los catalizadores presentan un bajo desempeño en HDA y alta selectividad hacia la ruta de desulfurización directa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It is demonstrated that the above method of analysis fruitfully leads to better interpretation and advances in our knowledge of the structure of nanoporous materials. On the other hand, the strategies for the analysis presented in this paper seem particularly handy when dealing with materials that exhibit both micropores and mesopores, a type of materials often found in many scientific and industrial applications. ,,,,− …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is demonstrated that the above method of analysis fruitfully leads to better interpretation and advances in our knowledge of the structure of nanoporous materials. On the other hand, the strategies for the analysis presented in this paper seem particularly handy when dealing with materials that exhibit both micropores and mesopores, a type of materials often found in many scientific and industrial applications. ,,,,− …”
Section: Introductionmentioning
confidence: 99%
“…In this contribution, a critical assessment of the nitrogen adsorption–desorption isotherms of a series of materials based on amorphous aluminosilicates and of the data thereof derived to characterize their texture is done. The amorphous aluminosilicates were synthesized with three methods: sol–gel via hydrolysis in acidic medium (ACSG), , sol–gel with a poly­(ethylene glycol) (PEG) template (P), , and sol–gel with gel skeletal reinforcement (GRS). ,, All of these methods have proven to produce materials with different textures, namely, surface area (SA) and porosity. This property has made them interesting for catalytic applications either as standalone materials or as carriers for metallic catalytic phases of particular interest for hydrocracking processes. Besides specific procedures of the synthesis method, it is known that the Si/(Si + Al) molar ratio of the aluminosilicates and the loading of metallic phases may affect their texture. ,,, Herein, we particularly loaded the synthesized amorphous aluminosilicates with nickel and molybdenum oxide by wet impregnation. , These materials are normally applied for hydroprocessing reactions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…One is the direct desulfurization (DDS) route and the other is mediated by the hydrogenation of one of the aromatic rings (HYD) of the molecule before the breakage of its C-S bond. [16,18,19,[21][22][23][24][25][26] The direct desulfurization of dibenzothiophene is kinetically dominant over conventional -Al2O3 supported Ni-MoS2 and Co-MoS2 catalysts and even over unconventional noble metal promoted MoS2 catalysts. [26][27][28][29][30][31][32][33][34][35] Accordingly, it is generally agreed that MoS2 is the active phase of the catalysts and that secondary metals such as Ni, Co, and even noble metals essentially act as promoters of the MoS2.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies for analysis presented in the paper seem particularly handy when dealing with materials that exhibit both micropores and mesopores; a type of materials often found in many scientific and industrial applications. 19,35,36,[38][39][40][41][42][43][44][45][46][47][48] 2. Experimental and analytical methods 2.1 Analyzed materials.…”
Section: Introductionmentioning
confidence: 99%
“…Further impregnation of a Ni-MoOx phase was made to these amorphous silica-aluminas (NiMo) whose primary application was the refining of heavy crude oil cuts. 44,45 Specific details for the synthesis of the materials are reported by Coconubo 36 and Duarte. 35 For the purposes of the current work, the materials were branded as ASA###, ASAP##, ASAR###, and NiMo/ASA###, NiMo/ASAP##, and NiMo/ASAR###.…”
Section: Introductionmentioning
confidence: 99%